CARBOHYDRATES OF CHANGES DURING THE FOLLICULAR DEVELOPMENT IN THE OVARY OF THE MOUSE DEER, TRAGULUS JAVANICUS - -, Hamny; Agungpriyono, Srihadi; Djuwita, Ita; Nisa, Chairun; Esthi Prasetyaningtyas, Wahono; Rahmi, Erdiansyah (Jurnal Veteriner; Vol 9 No 1 (2008))
The data available on the female reproductive organ of mouse deer (Tragulus javanicus) is still very limited. A study was therefore conducted to investigate the distribution and the concentration of carbohydrate residues during the development of ovary follicles. An ovary at luteal phase was used in this study. Thin sections of the ovary were prepared occording to the standard methods and they were then histochemically stained with flourecnece-labelled lectins such as peanut agglutinin (PNA), Ricinus communis agglutinin (RCA), Concanavalin A (Con A), Winged bean agglutinin (WGA) and Ulex europaeus agglutinin (UEA). The result showed that changes in the distribution and the concentration of carbohydrate occured during the development of the follicle. During the preantral stage, the cytoplasm of oosit contained carbohydrate with the residues of glucosa dan mannosa. Zona pelusida contained carbohydrates with residues of glucosa, mannosa, galactosa dan N-asetylgalactosamine, whereas extracellular matrix contained carbohydrate with the residues of glucosa dan mannosa. In the antral follicle, the cyitoplasm of oocytes contained carbohydarte with the residues of galactosa dan N-asetylgalactosamine, whereas its zona pelusida, extracellular matrix and follicular fluid contained carbohydarte with the residues of fucosa, N-asetylglucosamin and cyalic acid. Diffrences in the types and the distribution pattern of carbohydrates were observed in this study, both in preantral and antral follicles.
Keywords: ovary, follicles , deer, lectins, histochemistry